Empirical prediction of the in-plane/out-of-plane interaction effects in clay brick unreinforced masonry infill walls. (15th January 2021) - Di Domenico, Mariano; De Risi, Maria Teresa; Ricci, Paolo; Verderame, Gerardo M.; Manfredi, Gaetano
Highlights: Three experimental tests on the IP/OOP interaction on square infill walls are presented. A wider experimental database is collected including these test results. The effectiveness of existing proposals to predict the IP/OOP interaction is assessed. The influence of infill geometric properties and IP damage level is analyzed. New empirical formulations are proposed for the OOP strength and stiffness reduction. Abstract: The out-of-plane (OOP) response of unreinforced masonry (URM) infill walls under seismic loading has been widely studied in very recent times with both experimental and numerical investigations. It is recognized that the damage of infills due to in-plane (IP) seismic actions has a significant influence on their OOP response, by reducing the OOP strength and stiffness: this phenomenon is named IP/OOP interaction. Current code provisions propose the use of formulations derived from the literature to predict the OOP strength reduction due to IP damage. In this study, experimental tests are performed to assess the IP damage effects on the OOP response of square URM infills with relatively low slenderness ratio in reinforced concrete frames. Tests' results are used to enrich the currently available experimental database, to assess the effectiveness of current provisions regarding the prediction of the IP/OOP interaction effects and to propose empirical formulations for the prediction of the IP/OOP interaction effects in terms of OOP strength and stiffness reduction as a function of geometric properties of the infill (namely, the slenderness ratio and the aspect ratio) and of the IP displacement demand.